Collisional broadening of Kr (4p6S01→→5p[32]2) transition with combustion species as collision partners. (May 2016) - Zelenak, Dominic; Sealy, William; Narayanaswamy, Venkateswaran
Abstract: Collisional broadening of krypton 4 p 6 S 0 1 → → 5 p [ 3 2 ] 2 transition centered at 107.3 nm caused by common combustion species is investigated in this work. The present work investigates the compositional and thermodynamic dependencies of the collisional parameters between collision partners with similar electronic energy level gaps. In this situation, the classical expression of dispersive energy during collisions cannot be simplified to obtain closed form equations for the collisional parameters. The broadening parameters, namely collisional full width at half maximum ( w c ) and collisional shift ( δ c ) are obtained through a two-photon excitation scan of krypton (Kr) present in a mixture containing krypton and the collision partner at 295 K and 101 kPa. The compositional scaling of w c and δ c are compared with scaling at situations corresponding to both large and small perturber electronic energy level gaps as compared to the absorber's electronic energy level gap. In the Kr PLIF system, w c scaling corresponds to a situation where the perturber electronic energy level gap is significantly larger than absorber energy level gap, whereas δ c scaling corresponds to when the absorber electronic energy level gap is significantly larger than the perturber electronic energy level gap. Further, contributions from non-dispersive forces are computed to be significantly smaller than dispersive forces, which results to the observed tight scaling. The observed compositional scaling is shown to be consistent with a different collisional partner system (NO as the absorber and combustion species as perturbers), indicating that the scaling obtained with the krypton system is general to situations with perturbers and absorbers having similar electronic energy level spacing. Highlights: Compositional scaling of collisional full width at half-maximum (FWHM) and shift are compared with scaling at situations corresponding to both large and small perturber electronic energy level gaps as compared to the absorber's electronic energy level gap. In the Kr-PLIF system, collisional FWHM and shift scale to large and small perturber electronic energy level gaps when compared to that of the absorber, respectively. Contributions from non-dispersion forces are negligible and result in the apparent tight scaling of collisional FWHM and shift for various perturbers in the Kr-PLIF system. The observed compositional scaling is general for other absorber/perturber combinations with similar electronic energy level gap differences (NO as absorber and combustion species as perturbers), with findings provided from previous studies.